PAI (Islamic Religious Education) Teacher in Facing The Millenial Era Challenges - Amaly, Abdul Mun'im; Ruswandi, Uus; Muhammad, Giantomi; Erihadiana, Muhammad (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2022)
The 21st century, known as the millennial era, cannot be separated from technological advances and other advances that cannot be denied. However, many PAI (Islamic Religious Education) teachers are less capable and less ready to face students in this millennial era. Therefore, the researchers examined PAI teachers' readiness to meet the millennial era's challenges using the library research method taken from various indexed scientific journals. Then, the researchers analyzed the data using the content analysis method. Research result showed that the challenges of Islamic religious education teachers in the millennial era are related to technology and the process of education that cannot be separated from character education that upholds the values of Islamic teachings by applying technology-based learning. Teachers as role models of a religious character and have an optimistic attitude in developing personality according to Islamic principles. So it can be concluded the Islamic religious education teachers are dynamic and open in absorbing various technologies and information that will support their competence. With teachers' adaptive competence, students in this millennium era are expected to master multiple skills and have clean hearts, minds, and noble characters.